Innovative Instruments in Ukrainian Scientific Communication - Nazarovets, Maryna (Current Issues of Mass Communication, 2017)
The development of information technologies has led to changes in the processes of scientific communication and role of library support of research processes. Librarians from the Utrecht University (the Netherlands) Jeroen Bosman and Bianca Kramer conducted a global online survey “Innovations in Scholarly Communication” to study the situation. The main objective of this our study is to identify the main trends in the usage of modern communication tools by Ukrainian scientists with the help of analysis of responses of 117 Ukrainian respondents who took part in this online survey.